Deposition of nanosilica particles on fiber surface for improving interfacial bond and tensile performances of ultra-high-performance fiber-reinforced concrete. (15th September 2021) - Oh, Taekgeun; You, Ilhwan; Banthia, Nemkumar; Yoo, Doo-Yeol
Abstract: This study aimed to improve the interfacial bond and tensile performance of ultra-high-performance concrete (UHPC) containing steel fibers by modifying the fiber surface using an ethylenediaminetetraacetic acid (EDTA) electrolyte solution, cold gas plasma, and nanosilica (SiO2 ) coating. The test results indicate that the surface roughness of the steel fiber significantly increased because of the chelate effect through the EDTA electrolyte solution and the deposited nanosilica particles. The root mean square roughness, R q, of the plain fiber sample increased by approximately two and nine times owing to the EDTA treatment and nanosilica coating, respectively. The roughened surface was more effective in enhancing the pullout resistance than the increase in surface energy, and the nanosilica coating further increased chemical adhesion and frictional shear stress, significantly increasing bond strengths and pullout energy, owing to the densified interface by the pozzolanic reaction. The tensile performance of UHPC containing steel fibers could be improved by the chelating effect of the EDTA electrolyte solution and nanosilica coating. The EDTA-treated fiber sample with nanosilica coating thus provided the best tensile performance with a tensile strength of 20.3 MPa, strain capacity of 0.99%, and g -value of 159.1 kJ/m 3 .